Toni Wolff: Her Collaboration with C. G. Jung. (3rd April 2018) - Stephens, Stephani
ABSTRACT: Toni Wolff & C. G. Jung: A Collaboration by Nan Savage Healy is the first scholarly book about Jung's collaborator and lover Toni Wolff. Healy's thorough historical treatment addresses many of the questions that the Jungian community has had over the years regarding the nature of the relationship, both personal and professional, between Jung and Wolff and overlays Wolff's life alongside what we already know of Jung's.